COMMUNICATION AND SOCIAL MEDIA ACTIVITIES STUDY ON BENGKULU STUDENTS’ SOCIAL NETWORK SITES DURING PANDEMIC ERA - Budiman, Dwi Aji; Syukri Hamzah; Sarwit Sarwono; Didi Yulistio (Corolla International Conference, 2022)
This qualitative research aims to find out and explain how communication activities among students during the covid-19 pandemic through the use of social network sites. The results showed an increasing trend in the activity of using social media networks such as Facebook, Instagram, TikTok, among students in the pandemic period. Based on communication activities and social media use, students have a tendency to orient themselves as active users when determining the social network sites they choose. This shows that the learner finds satisfaction with fulfilling the message and the need for information for himself as explained through the model of uses and gratification theory, individual interest and freedom in determining social media determined by the student himself. Another finding, there is a tendency of consumptive patterns among students by accessing and making purchase transactions on goods they want through online shops, there is a tendency of dependency in the use of communication media with an average use of 5 to 6 hours per day, there is a popular orientation culture through interest in following Korean impressions and impersonation behavior on TikTok social media content.